1992
DOI: 10.1093/bja/68.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Vecuronium on Diaphragm and Geniohyoid Muscle in Anaesthetized Dogs

Abstract: We have examined the sensitivity of the geniohyoid, an upper airway dilating muscle, to vecuronium in 12 anaesthetized dogs undergoing mechanical ventilation of the lungs and compared it with that of the diaphragm. Dogs were allocated randomly to two groups: pentobarbitone alone (group 1, n = 7); pentobarbitone combined with 0.2 MAC (0.44%) of enflurane anaesthesia (group 2, n = 5). Supramaximal single twitch stimulations (0.1 Hz) were applied to the phrenic nerves in the upper thorax and the geniohyoid branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…[1][2][3][4][5] The masseter, genioglossus, and geniohyoid are upper airway muscles that play an important role in airway patency. It has been suggested that while inspiratory muscles have recovered their function, upper airway muscles may still be paralyzed predisposing to airway collapse at the end of anesthesia 6 . A previous study by D'Honneur and colleagues compared the effect of atracurium and vecuronium on the adductor pollicis muscle and the geniohyoid muscle in 16 patients.…”
Section: Editorial Comment: What This Article Tells Usmentioning
confidence: 99%
“…[1][2][3][4][5] The masseter, genioglossus, and geniohyoid are upper airway muscles that play an important role in airway patency. It has been suggested that while inspiratory muscles have recovered their function, upper airway muscles may still be paralyzed predisposing to airway collapse at the end of anesthesia 6 . A previous study by D'Honneur and colleagues compared the effect of atracurium and vecuronium on the adductor pollicis muscle and the geniohyoid muscle in 16 patients.…”
Section: Editorial Comment: What This Article Tells Usmentioning
confidence: 99%
“…13 Physiological studies show that the upper airway muscles are more sensitive to neuromuscular blocking drugs than either the diaphragm or the peripheral muscles. 14 Patients with OSA are highly vulnerable to medications that suppress pharyngeal muscle activity. [15][16][17] In addition to compromising upper airway muscle function, general anesthesia and narcotics can depress the patients' ventilatory responses to obstruction and inhibit their normal arousal and awakening responses to hypoxia and hypercapnia.…”
Section: Résumémentioning
confidence: 99%
“…The upper airway dilator muscles deliver these dilating forces, but it is largely unknown whether this balance is maintained during recovery from neuromuscular blockade. It has been shown in animals 21,23 and in humans 10,11 that up-per airway muscles are more susceptible to effects of neuromuscular blocking agents than the diaphragm. 11,21,23 Sundman and Eriksson 10 showed an increased incidence of misdirected swallowing and a decreased upper esophageal sphincter resting tone during minimal neuromuscular blockade (TOF ratio 0.5-1) that persisted even with recovery of the TOF ratio to unity.…”
Section: Discussionmentioning
confidence: 99%